(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to find out and to compare the effect of cholecystectomy performed due to gallstone on the extrahepatic bile ducts morphometry in diabetic and non-diabetic patients.Material and Methods: Three groups consisting of a total of 120 individuals. Diabetic patients with cholelithiasis (DC group) consisted of 40 person, non-diabetic patients with cholelithiasis (N-DC group) consisted of 40 person and healthy group (H group) consisted of 40 person. Laparoscopic cholecystectomy was performed on individuals with cholelithiasis.DHC (ductus hepaticus communis) diameter was measured below hepatic canal bifurcation from mucosa to mucosa by ultrasonography. The measurements were conducted in preoperative period and in the third and sixth postoperative months. Results: There were no significant differences between DC and N-DC groups in terms of DHC diameters in preoperative period and postoperative third and sixth months. In both DC and N-DC groups, DHC diameters in postoperative third and sixth months were found to show a small but statistically significant increase.Conclusion: This study showed a small but statistically significant dilatation in DHC following cholecystectomy. In addition, no statistically significant difference was found between DC and N-DC groups in terms of post- cholecystectomy DHC dilatation.